(untitled) (Journal of Comparative Social Work, 2017)
This article about social workers in the public social services in Brazil explores professional social work practice through the subjective standpoint of the social workers. Inspired by institutional ethnography, this approach explicates how understandings of social work are interpreted and implemented in various contexts. The findings show that the formalization of the relationship with the employer through contracts of employment implicate that the disciplinary normative definitions of social work succumb to institutional regulations, which are not necessarily discipline specific. In addition, the temporary character of the contracts of employment makes the social workers align their practice to institutional frameworks and demands, as they are personally interested in renewal of the contracts and the maintenance of their professional careers. With this approach, disciplinary, political, ideological, legal and moral definitions of social work are not viewed as the essences of social work, but rather as contextual processes that are locally activated in different contexts. At the same time, it underscores social work as a political profession which should naturally include interventions on political, juridical, economic and organizational levels. Consequently, professional social work is not one thing, nor only one profession, but rather professional practices adapted to a variation of contexts. This perspective is significant to help detect areas of intervention for social change.